Deliberative origins and concepts - Abdiche, Fatiha (Journal of Human Sciences, 2022)
The deliberation is the science that studies the actual use of language, that is, it studies the language within its communicative framework. It is the subject of communication and communication and the elements of objectivity and benefit. The deliberation emerged from the philosophy of analytic analysis, specifically the philosophy of ordinary language by Austin and Searle. And the acts of speech, a theory that studies verbal acts and classifies them according to the standards of truth and lies or lack thereof, and although the deliberation of Western origin, but we find our Arab scientists have been interested and show their implications in our Arab heritage, through their interest in the phenomena of news and construction, Verbal acts and adopted in their study of the speech on the same tools used by Altdaulion Kahtmamanm Balmkhatab and the addressee and the context of the case, the purpose of the speaker, benefit hearer, the relationship between the listener and the offeree linguistic acts and other tools that help in understanding the speech and the success of the communicative process.